The concept of moñ as an element of the Tatar Cosmo-Psycho-Logos: intellectual and poetic discourses - Amineva, Venera R.; Shaimerdinova, Nurila G. (The New Research of Tuva, 2024)
The article analyzes the key concept of Tatar culture “moñ”, a parameter of national identity — from the perspective of its specific functions in literature, particularly in early 20th-century Tatar poetry. Understanding “moñ” requires a multifaceted approach, like other concepts with distinctive semantic and figurative fields that lack an adequate verbal equivalent in other languages. The concept is examined from linguistic, art historical, religious-philosophical, ethnopsychological, and literary-aesthetic perspectives, which allow for a comprehensive view of its integrative nature across various contexts. Using the example of early 20th-century Tatar poetry, the article reveals the epistemological potential of a functional approach in identifying both constant features within the structure of this concept and individual authorial representations of its semantic core. It is established that the content structure of “moñ” is shaped by the aesthetic perception of contemporary reality by Tatar literary classics (G. Tukay, Dardmend, Sh. Babich) and their moral-aesthetic evaluation of it. In Dardmend’s work, “moñ” acquires a universally philosophical dimension, while in Sh. Babich’s poetry, it also serves as a musical element within the text. The study concludes that “moñ” characterizes a distinctive feature of the Tatar national “Logos”. It reflects an understanding of human destiny, national-historical reality, and the events of cultural mythology as a unified whole. As an element of national character (“Psyche”), “moñ” becomes part of a system of principles and techniques for psychological portrayal, serving as a summative, generalized designation of the characters’ stable emotional-psychological states. Finally, “moñ” also appears as a natural-cosmic backdrop (“Cosmos”), objectifying the intense lyrical experiences of the tragic fate of both the individual and the nation.